EVALUATION OF WATER QUALITY INDEX OF THE BRASS RIVER, BAYELSA STATE, SOUTH-SOUTH, NIGERIA - K. E, Leizou; J. O, Nduka; A.W, Verla (International Journal of Research -GRANTHAALAYAH, 2017)
The purpose of this study is to evaluate some major physical, chemical variables and heavy metals in water of the Brass River, Bayelsa State, South-South, Nigeria and assess the potential ecological risk. The variables investigated were: pH, EC, turbidity, TDS, TSS, Cl- , SO2-4, HCO- 3, TH, TA, Ca2+, K and Mg2+ , while the heavy metals were: Mn, Pb, Zn, Cu, Fe, Cd, Ni and Cr respectively. The results showed that pH, EC, TDS, Cl-, SO4, TA, TH, Na and K were appreciably high and the heavy metals: Fe, Pb, Zn, Cu and Cd, Ni was found at low concentration, Cr and Mn was below detection limits (BDL). Water quality index (WQI) was computed in order to assess suitability to beneficial purposes and assess the potential ecological risk of the Brass River. The results obtained on WQI from the four sampling stations (Mouth, Upstream, Downstream and Middlestream) fluctuate from 84.13 to 86.36. Hence, the Brass River water quality is considered good based on the water quality index (WQI). A comparative analysis of this study with FEPA, CCME standards for brackish water revealed that the results obtained in this study were within the permissible limits and concomitant with documented studies from similar environments.